2015
DOI: 10.1515/helmin-2015-0038
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of the composition and structure of parasite communities of red porgy, Pagrus pagrus (Perciformes: Sparidae) off Brazil

Abstract: SummaryA study of seasonal variation of metazoan parasite community of Pagrus pagrus was conducted between January and December 2012. Two hundred forty specimens of Pagrus pagrus were collected in four seasons (autumn and winter in dry season and spring and summer in rainy season) from off the state of Rio de Janeiro, Brazil. Twenty one species of metazoan parasites were found, with larvae of Hysterothylacium sp. being the dominant species. The highest values of prevalence and abundance was during the rainy se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Examination of the specimen from P. pagrus identified as E. spari (CHIOC 34531) [23] showed that it belongs to the new species. Specimens found previously in the same host [25] also belong to the new species.…”
Section: Differential Diagnosismentioning
confidence: 58%
See 1 more Smart Citation
“…Examination of the specimen from P. pagrus identified as E. spari (CHIOC 34531) [23] showed that it belongs to the new species. Specimens found previously in the same host [25] also belong to the new species.…”
Section: Differential Diagnosismentioning
confidence: 58%
“…The following species of Encotyllabe have been recorded from marine fishes in Brazil: Encotyllabe spari in Haemulon sciurus, Orthopristis ruber, Anisotremus surinamensis, Conodon nobilis (Haemulidae), Pagrus pagrus (Sparidae), Menticirrhus americanus, Micropogonias furnieri (Sciaenidae) and Dactylopterus volitans (Dactylopteridae), Encotyllabe cf. spari in O. ruber, Encotyllabe lintoni in P. pagrus, and Encotyllabe souzalimae in Trichiurus lepturus (Trichiuridae) and Thyrsitops lepidoides (Gempylidae) [4,11,[16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the Laboratory of Evolutionary Helminthology from USP includes a productive group focusing on the taxonomy of cestodes parasitic in Chondrichthyes (Marques et al ., 2012; Marques & Reyda, 2015). It is also important to highlight the activity of researchers from UFRRJ in several studies on the ecology of parasites from fish (Amarante et al ., 2015; Soares & Luque, 2015), which is a subject equally explored by the research group from the Laboratory of Ichthyoparasitology, UEM, State of Paraná (southern Brazil) (Bellay et al ., 2015a, b). Also in Paraná, the group formed by researchers from the Department of Zoology of the UFPR, have produced one of the most impressive collections of literature on the morphological and molecular taxonomy of monogeneans (Boeger et al ., 2014b, 2015).…”
Section: Current Research Groups and Their Geographic Distributionmentioning
confidence: 99%
“…With regard to the Brazilian records, E. spari (but also E. cf. spari) has been recorded from at least four species of Haemulidae, Conodon nobilis, Anisotremus surinamensis, Haemulun sciurus and Orthropristis ruber; one species of Sparidae, Pagrus pagrus (Sparidae); two species of Sciaenidae (Menticirrhus americanus, Micropogonias furnieri); and one species of Dactylopteridae (Dactylopterus volitans) [15,16,20,22,25,26] (Table 3). Our data challenge the low host speci city of Encotyllabe from Brazil; worms from the Sparid Pagrus and those from the Haemulid Orthopristis ruber belong to different species, as demonstrated by molecular tools (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The following species of Encotyllabe have been recorded from marine sh in Brazil: Encotyllabe spari in Haemulon sciurus, Orthopristis ruber, Anisotremus surinamensis, Conodon nobilis (Haemulidae), Pagrus pagrus (Sparidae), Menticirrhus americanus, Micropogonias furnieri (Sciaenidae) and Dactylopterus volitans (Dactylopteridae); E cf. spari in O. ruber; E. lintoni in P. pagrus; and E. suozalimae in Trichiurus lepturus (Trichiuridae) and Thyrsitops lepidoides (Gempylidae) [7,[15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%